Potensi Muffin Cinnamon sebagai Pangan Fungsional terhadap Sifat Organoleptik dan Kandungan Gizi (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2023)
Muffin processing using banana flour can produce good characteristics and increase nutritional value. The use of cinnamon in muffin products is difficult to find in the market. The characteristics of cinnamon have a fragrant and sweet aroma. Cinnamon contains the highest antioxidants compared to other types of spices. Muffin products developed with banana flour with the addition of cinnamon certainly have functional properties. The study aimed to determine the organoleptic properties of muffin products with the addition of cinnamon powder including color, aroma, taste, texture and overall acceptance and to analyze the nutritional content of muffins so that can be used as food diversification and accepted by society. Quantitative research used a single factor Completely Randomized Design. The results showed that the addition of cinnamon powder had an effect on color, aroma, texture and overall acceptability, but had no effect on the taste of cinnamon muffin products. Based on the results of the organoleptic test, the best nutritional content was found in the P3 treatment with 24.72% a moisture content, 51.46% carbohydrates, 1.07% ash, 14.42% fat and 8.33% protein. The amount of cinnamon powder affects the organoleptic properties and nutritional content. Muffin processing using banana flour can produce good characteristics and increase nutritional value. The use of cinnamon in muffin products is difficult to find in the market. The characteristics of cinnamon have a fragrant and sweet aroma. Cinnamon contains the highest antioxidants compared to other types of spices. Muffin products developed with banana flour with the addition of cinnamon certainly have functional properties. The study aimed to determine the organoleptic properties of muffin products with the addition of cinnamon powder including color, aroma, taste, texture and overall acceptance and to analyze the nutritional content of muffins so that can be used as food diversification and accepted by society. Quantitative research used a single factor Completely Randomized Design. The results showed that the addition of cinnamon powder had an effect on color, aroma, texture and overall acceptability, but had no effect on the taste of cinnamon muffin products. Based on the results of the organoleptic test, the best nutritional content was found in the P3 treatment with 24.72% a moisture content, 51.46% carbohydrates, 1.07% ash, 14.42% fat and 8.33% protein. The amount of cinnamon powder affects the organoleptic properties and nutritional content.